The Effect of Airport Service Innovation on Customer Satisfaction and Increasing Customer Value - Zainita Sarah; Raissa Putri Ramadhani; Haris Haris; Lut Mafrudoh (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study explores the impact of service innovation on customer satisfaction, with customer value acting as an intervening variable at Soekarno-Hatta International Airport. This research focuses on three primary variables: Service Innovation (X1), Customer Value (Z), Customer Satisfaction (Y). This study uses quantitative research methods with Sem-PLS analysis techniques, with data collected from100 respondents who had experience using airport technology services on both international and local flights. These findings reveal that Service Innovation (X1) positively affects both Customer Satisfaction (Y) and Customer Value (Z). Moreover, Customer Value (Z) significantly influences Customer Satisfaction (Y). The results also demonstrate that Service Innovation (X1) has an indirect positive effect on Customer Satisfaction (Y) through Customer Value (Z). This research highlights the importance of service innovation in improving the overall customer experience and value perception, thus enhancing passenger satisfaction at airports.